Investment in precious metals in Ukraine - Bartysh, D. (ТДАТУ, 2018)
EN: In the article considered the most common ways of investment into precious metals and defined their peculiarities, advantages and disadvantages. UK: У статті розглянуті найбільш поширені шляхи інвестування в дорогоцінні метали та визначено їх особливості, переваги та недоліки.
Keywords: інвестування; дорогоцінні метали; investment; precious metals